2012
DOI: 10.1007/s00449-012-0871-5
|View full text |Cite|
|
Sign up to set email alerts
|

Batch and fed-batch growth of Pichia pastoris under increased air pressure

Abstract: Pichia pastoris CBS 2612 behavior under air pressures of 1, 3 and 5 bar in culture media of glycerol (pure and crude) and methanol was studied. Generally, the increase in oxygen transfer rate due to the increase of total pressure improved cellular growth for all carbon sources and for batch and fed-batch processes with different feeding rate strategies. In batch cultures, 1.4-, 1.2-, and 1.5-fold improvement in biomass production was obtained with the increase of air pressure up to 5 bar, using methanol, pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“… The values of OTR max were obtained from Lopes et al for the same hyperbaric bioreactor used in this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The values of OTR max were obtained from Lopes et al for the same hyperbaric bioreactor used in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The OTR from the gas phase into the medium is controlled by the oxygen solubility and the volumetric oxygen mass transfer coefficient ( K L a). The oxygen solubility in the liquid medium can be raised by increasing the total air pressure in the cultivation system, since this parameter is affected by the oxygen partial pressure and, consequently, by the total pressure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopes et al observed a 2.3‐fold increase of OTR in a bioreactor without mechanical agitation by shifting the total air pressure from 2 to 8 bar. In addition, in a mechanical stirred bioreactor, a threefold improvement in OTR by increasing air pressure from 1 to 5 bar was reported …”
Section: Introductionmentioning
confidence: 98%
“…Several other yeast species different from S. cerevisiae , such as Kluyveromyces marxianus , Candida utilis , and Pichia pastoris , were cultured under increased air pressure and it was proved possible to overcome the oxygen limitation and to improve cellular growth. The ethanol production was considerably reduced in K. marxianus (“Kluyver‐negative”) batch cultures under 6 bar of air pressure, and in C. utilis fed‐batch process at 12 bar of air pressure .…”
Section: Introductionmentioning
confidence: 99%